ยุทธศาสตร์การสร้างพลังผ่านพื้นที่สื่อของขบวนการทางสังคมในประเทศไทย - วารุณี ณ นคร (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The purpose of this study is to examine the power construction of social movement using mediascape of 3 case study were : the Assembly of the Poor of Rasi Salai Dam, Conversation Network of Bangkuntien, Bangkok and Klong Yong Cooperratives. The finding show the social movement used public mediascape to broaden public support and to make an impact on policy makers by framing tactics. Mutual understanding and sympathy from the public were created in order to be the witnesses in the social movement.The condition for success of these marginal people in using the right to communicate were : 1) advanced technology and the ability to access technology, 2) the use of social networking, 3) media reform in Thailand, which has generated varied communication channels especially broadcasting and online media.